High Prevalence of Multidrug-Resistant Tuberculosis, Swaziland, 2009–2010 - Sanchez-Padilla, Elisabeth; Dlamini, Themba; Ascorra, Alexandra; Rüsch-Gerdes, Sabine; Tefera, Zerihun Demissie; Calain, Philippe; de la Tour, Roberto; Jochims, Frauke; Richter, Elvira; Bonnet, Maryline (Emerging infectious diseases, 2012)
In Africa, although emergence of multidrug-resistant (MDR) tuberculosis (TB) represents a serious threat in countries severely affected by the HIV epidemic, most countries lack drug-resistant TB data. This finding was particularly true in the Kingdom of Swaziland, which has the world's highest HIV and TB prevalences. Therefore, we conducted a national survey in 2009-2010 to measure prevalence of drug-resistant TB. Of 988 patients screened, 420 new case-patients and 420 previously treated case-patients met the study criteria. Among culture-positive patients, 15.3% new case-patients and 49.5% previously treated case-patients harbored drug-resistant strains. MDR TB prevalence was 7.7% and 33.8% among new case-patients and previously treated case-patients, respectively. HIV infection and past TB treatment were independently associated with MDR TB. The findings assert the need for wide-scale intervention in resource-limited contexts such as Swaziland, where diagnostic and treatment facilities and health personnel are lacking.